Phenotypic identification of Penicillium spp. isolated from clinical wastes based on microstructure characteristics - Ali Noman, Efaq; Al-Gheethi, Adel Ali; Nik Ab. Rahman, Nik Norulaini; Hideyuki, Nagao; Haji A Talip, Balkis; Radin Mohamed, Radin Maya Saphira; Ab. Kadir, Mohd. Omar (Malaysian Society for Microbiology, 2018)
Aims: The present study aimed to recognize the microstructure of conidiophores and spores of Penicillium spp. which were isolated from clinical wastes. Methodology and results: The isolates of Penicillium spp. were obtained from the solid clinical wastes on V8A medium and purified by single spore method. The culture characteristics were described in five culture media included; Czapek Yeast Extract Agar (CYA); Malt Extract Agar (MEA), Potato Dextrose Agar (PDA), Sabouraud Dextrose Agar (SDA) and Czapek-Dox Agar (CZ) while the conidiophores and spores were described using light and Scanning Electronic Microscope (SEM). Penicillium spp. observed some differences in their culture characteristics. Among 11 Penicillium species isolated in this study and identified based on culture and microscope morphology. Five species including P. simplicissium, P. waksmanii, P. corylophilum and P. decumbens as well as one species identified as T. wortmannii were described in detail using SEM. Conclusion, significance and impact of study: The study revealed that the microstructure of the fungal spores and conidiophores play an important role in the taxonomy of fungi species based on the phenotypic method.